Lafaz Muá¹laq dan Muqayyad dalam Perspektif Uá¹£Å«liyyah: Telaah Makna, Penerapan dalam Nas, dan Implikasi Hukum - Nico Akbar; Fatmawati F; Abd. Rauf Muhammad Amin (Media Hukum Indonesia (MHI), 2026)
The Qurâ€™an, as the primary source of Islamic law, employs a rich, diverse, and nuanced language. Among the forms of expression found within it are muá¹laq (unrestricted) and muqayyad (restricted) terms. A proper understanding of these concepts is essential, as legal rulings in the Qurâ€™an and Hadith are often conveyed either in an unrestricted (muá¹laq) or a restricted (muqayyad) form. Classical scholars of uá¹£Å«l al-Fiqh have long examined the interaction between these two types of expressions, particularly when two legal texts address the same issue but differ in formulation one being muá¹laq and the other muqayyad. Scholarly debates also arise in cases where the legal ruling is the same but the underlying cause differs, or conversely, where the cause is the same but the ruling differs. This demonstrates the complexity of the methodology of Islamic legal derivation, which requires careful analysis of linguistic expressions, contextual considerations, and supporting evidences. Therefore, understanding muá¹laq and muqayyad is not only crucial in the theoretical domain of uá¹£Å«l al-Fiqh, but also carries practical implications in fiqh, particularly in the process of legal ijtihÄd that remains relevant to the evolving needs of the Muslim community.